Innovation and Entrepreneurship: A Colour Economy Glance - Estrada Salvador; Montalván-Burbano Néstor; Cabrera-Flores Mayer; León-Pozo Alicia; Rueda-Prieto John Alexander (SHS Web of Conferences)
This article introduces the topic of the Colour Economy as a set of new economic paradigms that seek to respond to global challenges such as sustainability, technological transformation and social inclusion. It is a first comprehensive study that analyses eight colour economies, namely blue, yellow, orange, red, green, silver, purple, and grey with a focus on innovation and entrepreneurship. The researchers started from a bibliographic search that yielded varied results in terms of the volume of literature produced on the colour palette and opted for an exploratory and critical study of the concepts and relationships with innovation and entrepreneurship. We found that each colour economy addresses specific issues but converges on themes such as sustainability, technological transformation and social equity. Our review revealed that colour economies are not mere theoretical constructs but practical frameworks that focus on the sustainable use of marine resources, in the case of the Blue Economy, the Yellow Economy emphasizes technological efficiency, while the Orange Economy emphasizes creative and cultural industries, the Red Economy, on the other hand, comes from the evolution of consumption towards sustainable practices, and in the Green Economy, the priority is on environmental sustainability, while the Silver Economy focuses on the challenges of an aging population, as opposed to the Purple Economy, which promotes cultural and social diversity, and the Grey economy is embedded in the informal sector. In terms of their relationship to innovation and entrepreneurship, each colour economy presents unique paths to innovation and entrepreneurship opportunities. In all economies of colour, cross-sector collaboration between government, business and academia is key to driving innovation. Our study presents a novel framework for analysing economic transformation through the lens of the colour economy where the colour family does not compete for theoretical or practical supremacy but rather opts for a complementary effect to address the enormous global challenges we face. Thus, the framework developed offers important and valuable insights for policy makers, businessmen and entrepreneurs as well as scholars to develop a holistic and integrated approach to economic development.